A new ancient leiobunine genus and species from the Russian Northwest Caucasus (Opiliones: Sclerosomatidae). Issue 4 (2nd October 2022) - Martens, Jochen; Wijnhoven, Hay
Abstract : A new genus and species of harvestman belonging to the family Sclerosomatidae from the Russian Northwest Caucasus is proposed: Amilenoides caucasicus n. gen., n. sp. This species has unusual male penial characteristics, which are judged as plesiomorphic traits within subfamily Leiobuninae. The relationships on subfamily level are discussed. This new species may be a relict of early sclerosomatid evolution. http://www.zoobank.org/urn:lsid:zoobank.org:pub:6796D1B3-46A6-486D-94BD-5F0AB1212F7D